Chemotaxonomic Profile and Intraspecific Variation in the Blow Fly of Forensic Interest Chrysomya megacephala (Diptera: Calliphoridae) - Paula, Michele C.; Antonialli-Junior, William F.; Mendonça, Angélica; Michelutti, Kamylla B.; Eulalio, Aylson D M M; Cardoso, Claudia A L; de Lima, Thiago; Von Zuben, Cláudio J (Oxford University Press (OUP), 2017)
Necrophagous insects such as blow flies (Diptera: Calliphoridae) are considered crucial in forensic entomology. Identification at species level and determination of larval stage are the basis for estimation of postmortem interval (PMI). Insect evidence can also be used in the determination of crime scenes, since body displacement is common. The aim of this study was to determine the chemotaxonomic profile and intraspecific variability of the forensically important blow fly Chrysomya megacephala (F. 1794). Adults were collected in the municipalities of Dourados-MS (Brazil) and Rio Claro-SP (Brazil), and then transferred to the laboratory for oviposition and development of the immature stages. Chemical analysis of cuticular compounds was performed by gas chromatography. Cuticular chemical profiles varied significantly between the two populations, as well as between developmental stages, supporting the use of these compounds as a complementary tool to help identify the species and its stages, along with geographical variability. This could greatly accelerate forensic investigations, eliminating the need to allow the fly larvae to develop until adult stage in order to confirm the species identity and sample origin.
Keywords: cuticular hydrocarbon; developmental stage; postmortem interval